2000
DOI: 10.1016/s0167-9236(00)00097-x
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the use of concept spaces to improve medical information retrieval

Abstract: This research investigated the application of techniques successfully used in previous information retrieval research, to the more challenging area of medical informatics. It was performed on a biomedical document collection testbed, Ž . CANCERLIT, provided by the National Cancer Institute NCI , which contains information on all types of cancer therapy. The quality or usefulness of terms suggested by three different thesauri, one based on MeSH terms, one based solely on Ž . terms from the document collection, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 15 publications
0
19
0
Order By: Relevance
“…[2] uses only a set of lists whose quality is high and contains a large number of terms. However, many lists that are shorter and may contain more heterogeneous pieces of information exist on the web.…”
Section: Methodsmentioning
confidence: 99%
“…[2] uses only a set of lists whose quality is high and contains a large number of terms. However, many lists that are shorter and may contain more heterogeneous pieces of information exist on the web.…”
Section: Methodsmentioning
confidence: 99%
“…Houston [10] compared 3 different thesauri for medical QE, consisting of corpus terms, MESH terms, and UMLS terms. He found no significant difference between them, but also little overlap, supporting a case for further exploration to discover the significant features of each term set, and use this information to combine their strengths.…”
Section: Related Workmentioning
confidence: 99%
“…To copy otherwise, or republish, to post on servers or to redistribute to lists, requires prior specific permission and/or a fee. JCDL'02, July [13][14][15][16][17]2002 according to the information sources utilized by the system, which they described as "community inputs". These include item attribute, external item popularity, purchase history, ratings, text comments and context/process information.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Since it has been shown that an asymmetric algorithm performs better than other clustering function like cosine function [13] to compute similarity for term associations, extending it to books is expected to improve precision as well. • tf ijk = tf ij when descriptor i appears in both book j and k , otherwise tf ijk = 0…”
Section: Similarity Computationmentioning
confidence: 99%
See 1 more Smart Citation